Aqueous Extract of Black Maca Prevents Metabolism Disorder via Regulating the Glycolysis/Gluconeogenesis-TCA Cycle and PPARα Signaling Activation in Golden Hamsters Fed a High-Fat, High-Fructose Diet - Wan, Wenting; Li, Hongxiang; Xiang, Jiamei; Yi, Fan; Xu, Lijia; Jiang, Baoping; Xiao, Peigen (Frontiers in Pharmacology, 2018)
Maca (Lepidium meyenii Walpers) has been used as a dietary supplement and ethnomedicine for centuries. Recently, maca has become a high profile functional food worldwide because of its multiple biological activities. This study is the first explorative research to investigate the prevention and amelioration capacity of the aqueous extract of black maca (AEM) on high-fat, high-fructose diet (HFD)-induced metabolism disorder in golden hamsters and to identify the potential mechanisms involved in these effects. For 20 weeks, 6-week-old male golden hamsters were fed the following respective diets: (1) a standard diet, (2) HFD, (3) HFD supplemented with metformin, or (4) HFD supplemented with three doses of AEM (300, 600, or 1200 mg/kg). After 20 weeks, the golden hamsters that received daily AEM supplementation presented with the beneficial effects of improved hyperlipidemia, hyperinsulinemia, insulin resistance, and hepatic steatosis in vivo. Based on the hepatic metabolomic analysis results, alterations in metabolites associated with pathological changes were examined. A total of 194 identified metabolites were mapped to 46 relative metabolic pathways, including those of energy metabolism. In addition, via in silico profiling for secondary maca metabolites by a joint pharmacophore- and structure-based approach, a compound-target-disease network was established. The results revealed that 32 bioactive compounds in maca targeted 16 proteins involved in metabolism disorder. Considering the combined metabolomics and virtual screening results, we employed quantitative real-time PCR assays to verify the gene expression of key enzymes in the relevant pathways. AEM promoted glycolysis and inhibited gluconeogenesis via regulating the expression of key genes such as Gck and Pfkm. Moreover, AEM upregulated tricarboxylic acid (TCA) cycle flux by changing the concentrations of intermediates and increasing the mRNA levels of Aco2, Fh, and Mdh2. In addition, the lipid-lowering effects of AEM in both the serum and liver may be partly related to PPARα signaling activation, including enhanced fatty acid β-oxidation and lipogenesis pathway inhibition. Together, our data demonstrated that AEM intervention significantly improved lipid and glucose metabolism disorder by regulating the glycolysis/gluconeogenesis-TCA cycle and by modulating gene expression levels involved in the PPARα signaling pathway.